User acceptance of web based groupware system: a case study at Terengganu Advanced Technical Institute (TATI) / Wan Roslina Wan Othman - Wan Othman, Wan Roslina (2006)
The groupware is increasingly being used as a way of implementing the organizational forms. The acceptance of groupware technology by Terengganu Advanced Technical Institute (TATI)'s user is a prerequisite for realizing its full potential in institution. Technology Acceptance Model (TAM) provides measurement scales for the perceived use fulness, perceived ease of use for user acceptance of the groupware system. Groupware being the supporting technology for groups at work need to be able to assist groups in communicating the challenges posed by the dynamic environment. The purpose of the study to identify the level of user acceptance, computer self efficacy and external variables towards the web based groupware system. The survey was carried out from academic and administration staff in TATI. In the survey, questions to the respondents on their perceptions of the acceptance level of the GWeb usage of perceived usefulness, ease of use and computer self efficacy. The results revealed that respondents rated all three performance measures favorably for GWeb. Specifically, they felt that GWeb was usefulness contribute neutrally to their work, easier, enhanced effectiveness on the work and improve work performance. GWeb was ease of use positively contribute on easy to learn, understandable and flexible to interact between group members. In addition to computer self-efficacy they feel neutrally confident to use computer at work or house when communicate and understand the GWeb system. Inspite of the respondents exhibited little resistance to their use in term of networking and management support. Finally, the results indicated that in general, GWeb's contribution level towards workgroup performance was viewed neutrally by these respondents.